Gamma irradiation as a tool for modification of graphene oxide-silver nanowires composites - Mišović Aleksandra (Proceedings of the International Symposium on Analytical and Environmental Problems, 2021)
Graphene oxide (GO) was produced using the Hummers' method while silver nanowires (AgNWs) were obtained by polyol synthesis. Composite was produced by simple mixing of GO and AgNWs dispersions. The composite was produced in a form of free/standing films by vacuum filtration and exposed to gamma irradiation in an oxygen-free atmosphere. After irradiation, without any additional cleaning, the structure, morphology and electrical properties were investigated. Gamma irradiation was shown to be an efficient tool to induce a chemical reduction of GO, and it was able to improve the electrical conductivity of produced composites. Due to avoiding the usage of reagents and solvents, this method belongs to green chemical approaches.